Engaging Religion in a Contested Age: Contestations, Postmodernity, and Social Change - Nesbitt, Paula D. (Sociology of religion, 2020)
Both secular and religious contestations have threatened the character of contemporary civic discourse, signifying underlying issues needing to be addressed. Postmodern and globalization influences have contributed to their scope and intensity, adding underlying complexities to the presenting issues. Drawing upon case examples of a secular plant closure in a racially and ethnically diverse company town and strife threatening organizational viability in the cross-cultural Anglican Communion, I argue first that religion either directly influences or indirectly serves as a latent resource within secularized morality, and second that cross-cultural contestations involving religion typically contain underlying societal concerns; both need to be addressed in analyzing meaning and hope for change. Sociologists of religion have opportunity to explore how religion is deployed as a moral basis of contestation, and how it might interact with postcolonial and other cultural dynamics, with implications for solutions in building social cohesion across worldviews and cultures.